2022
DOI: 10.3390/ijerph19031145
|View full text |Cite
|
Sign up to set email alerts
|

Oral Factors as Predictors of Frailty in Community-Dwelling Older People: A Prospective Cohort Study

Abstract: The purpose of this prospective cohort study was to identify predictors for frailty among possible oral factors in community-dwelling older people. Ninety-seven participants (≥60 years old) without frailty at baseline were included and assigned to either the robust or the frailty group after 2-year follow-up. The frailty was defined using the Japan Cardiovascular Health Study index. The numbers of present and functional teeth and periodontal disease severity were recorded. Bacterial counts on the dorsum of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…In support of these findings, periodontal disease has been associated with decline in grip strength 21 and physical frailty in later life. 43,44 Periodontal disease is an inflammatory disease that could lead to tooth loss. 45 The underlying systemic inflammation accompanying more acute periodontal disease (ie, before tooth loss) has been associated with poor physical fitness and capacity 46,47 and with a decline in lower extremity mobility, 48 which might result in reduced physical performance over time.…”
Section: Dentitionmentioning
confidence: 99%
“…In support of these findings, periodontal disease has been associated with decline in grip strength 21 and physical frailty in later life. 43,44 Periodontal disease is an inflammatory disease that could lead to tooth loss. 45 The underlying systemic inflammation accompanying more acute periodontal disease (ie, before tooth loss) has been associated with poor physical fitness and capacity 46,47 and with a decline in lower extremity mobility, 48 which might result in reduced physical performance over time.…”
Section: Dentitionmentioning
confidence: 99%
“…5,6 Additionally, OD reduction has been reported to be associated with general frailty. [7][8][9] This test is thus essential for assessing oral function in older adults. Some studies have reported a correlation between OD and cognitive function, with mild dementia being associated with OD.…”
mentioning
confidence: 99%
“…Table 3 shows the prospective associations between oral function and dysphagia at baseline and frailty, sarcopenia, and disability at follow-up in four prospective cohort studies [ 7 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…These two studies did not assess tongue pressure, tongue-lip motor function, and dysphagia. Takeuchi et al showed that the number of repetitions in ODK for /ta/ was a significant factor for developing frailty during a 2-year follow-up after adjusting for occlusal force, tongue pressure, EAT-10 score, ODK for /pa/ and /ka/, and other potential factors [ 40 ]. Tanaka et al showed that low occlusal force, ODK for /ta/, and tongue pressure at baseline were significant factors for the development of frailty during a 2-year follow-up after adjusting for potential factors [ 7 ].…”
Section: Resultsmentioning
confidence: 99%